2022
DOI: 10.1007/s12671-021-01797-0
|View full text |Cite
|
Sign up to set email alerts
|

The Two Arrows of Pain: Mechanisms of Pain Related to Meditation and Mental States of Aversion and Identification

Abstract: Objectives According to the core Buddhist psychology models of the “two arrows of pain” and “co-dependent origination,” pain is the resultant of bodily and mental factors, which can be regulated by meditation states and traits. Here we investigated how pain and the related aversion and identification (self-involvement) experiences are modulated by focused attention meditation (FAM), open monitoring meditation (OMM), and loving kindness meditation (LKM), as well as by meditation expertise. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…Secondly, we anticipate that this framework will replicate and unveil the nuanced dynamics of previous findings about the effect of mindfulness on pain regulation (12,13). Mindfulness meditation (MM) has a well-documented history of efficacy in chronic pain management (14,15), and has been shown to modulate acute pain perception among regular practitioners (13,16). Notably, a defining feature of MM and closely related techniques such as acceptance and commitment therapy (ACT) is to engage fully with the pain experience while reducing reactivity.…”
Section: Introductionmentioning
confidence: 78%
“…Secondly, we anticipate that this framework will replicate and unveil the nuanced dynamics of previous findings about the effect of mindfulness on pain regulation (12,13). Mindfulness meditation (MM) has a well-documented history of efficacy in chronic pain management (14,15), and has been shown to modulate acute pain perception among regular practitioners (13,16). Notably, a defining feature of MM and closely related techniques such as acceptance and commitment therapy (ACT) is to engage fully with the pain experience while reducing reactivity.…”
Section: Introductionmentioning
confidence: 78%
“…The (co)dependent origination model can be interpreted in terms of discrete momentary processes (Amaro, 2019), and in terms of a chain of cognitive and affective events or processing steps (see also Nicolardi et al, 2022). Specifically, these may be interpreted as follows: wrong views and 'ignorance', such as about the true nature of the self (avijjā in Pali; avidyā in Sanskrit) affect mental formations or states, such as motivational and emotional factors, as well as cognitive biases (saṅkhāra in Pali; saṃskāra in Sanskrit).…”
Section: The Model Of (Co)dependent Originationmentioning
confidence: 99%
“…Pain modulations have been extensively studied in healthy individuals ( Villemure et al, 2003 ; Rhudy et al, 2005 ; Valentini et al, 2017a , b ; Nicolardi et al, 2020 , 2022 ) and CP patients ( Bushnell et al, 2013 ; Yarnitsky, 2015 ). It has been reported that positive emotions and supportive social environments could decrease pain ( Che et al, 2018 ).…”
Section: Pleasant Touch In Chronic Pain Patientsmentioning
confidence: 99%